KONSEP BERKAH DI ERA GEMPURAN TRANSFORMASI DIGITAL : PERSPEKTIF AL-QUR’AN - Salewe, M Idman; Wardana, Elly (Ma'had Aly As'adiyah Sengkang, 2024)
Digital transformation has changed the way humans interact and behave, bringing significant impacts across various aspects of life. This paper explores the concept of blessings in the digital era from the perspective of the Qur'an, focusing on the challenges posed by artificial intelligence (AI) in education. While AI offers ease of access to information, reliance on technology can undermine the emotional connection between teachers and students, which is essential for a blessed learning process. This study aims to understand how Qur'anic values can serve as a guide for the wise use of technology and offer solutions to achieve blessings amidst the rapid wave of digital transformation. Thus, it is hoped that readers can navigate these changes based on principles aligned with Islamic teachings. Keywords: Digital Transformation, Concept of Blessings, Qur'an, Education, Artificial Intelligence.